The Ideology of Consumerism in Five Star Billionaire - Nina Farlina; Shabrina Farahiyah Febriyanti (Insaniyat : Journal of Islam and Humanities, 2019)
The last decades, people can calculate other people’s worth only through what they are wearing or their appearances. It makes the phenomenon of commodification and consumerism emerges in the society. This phenomenon might not harm the bourgeoisie, but it is harming the work class. This article discusses how consumerism harm the workers, meanwhile they are not realizing this. This phenomenon is clearly depicted by two main characters namely  Phoebe and Gary in Five Star Billionaire, a novel by Tash Aw created in 2013. The portrayal of commodification can be seen through the action of characters in seeing the object or the persons base on exchange and sign-exchange value. This research used qualitative method with Marxist theory about consumerism. The results show that Phoebe and Gary are treated as commodity that have exchange value. Next, Phoebe is used her fake-branded stuff to give other people impression. Last, Phoebe is using Walter Chao to make she lives in luxury. How Phoebe is commodifying her stuffs leads her to follow the ideology of consumerism.